2018
DOI: 10.3389/fphys.2018.01281
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Neuropeptide Y in Cardiovascular Health and Disease

Abstract: Neuropeptide Y (NPY) is an abundant sympathetic co-transmitter, widely found in the central and peripheral nervous systems and with diverse roles in multiple physiological processes. In the cardiovascular system it is found in neurons supplying the vasculature, cardiomyocytes and endocardium, and is involved in physiological processes including vasoconstriction, cardiac remodeling, and angiogenesis. It is increasingly also implicated in cardiovascular disease pathogenesis, including hypertension, atheroscleros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
132
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 146 publications
(143 citation statements)
references
References 159 publications
2
132
0
2
Order By: Relevance
“…27 NPY is a sympathetic cotransmitter and critical to cardiovascular homeostasis including cardiac remodeling and angiogenesis. 28,29 It has been correlated to stress, anxiety, and posttraumatic stress disorder 30,31 at a clinically relevant level of ≤1.5 ng/ml. 32 Our results showed that PRADA achieved highly sensitive detection of both biomarkers of acute myocardial infarction ideal for risk stratification.…”
mentioning
confidence: 99%
“…27 NPY is a sympathetic cotransmitter and critical to cardiovascular homeostasis including cardiac remodeling and angiogenesis. 28,29 It has been correlated to stress, anxiety, and posttraumatic stress disorder 30,31 at a clinically relevant level of ≤1.5 ng/ml. 32 Our results showed that PRADA achieved highly sensitive detection of both biomarkers of acute myocardial infarction ideal for risk stratification.…”
mentioning
confidence: 99%
“…In this study, we asked if NPY has an effect on DOXinduced cardiotoxicity. Previous studies have shown a diverse role for NPY in different types of cardiomyopathies, including an increase in NPY levels and effects on several pathological processes involved also in DOX-induced cardiotoxicity [11,30,[53][54][55][56]. Transgenic NPY overexpression had some effects on DOX-induced toxicity.…”
Section: Discussionmentioning
confidence: 91%
“…The demonstrated actions of NPY in the heart are extensive and affect the contractility of ventricular cardiomyocytes and the excitation-contraction coupling as well as cellular growth, blood supply, and neuronal control [9,10]. There is evidence linking NPY to different types of cardiovascular diseases with differential, even opposing, effects via diverse mechanisms [8,9,11]. We hypothesized that it may also play a role in DOX-induced cardiotoxicity.…”
mentioning
confidence: 99%
“…The observations made in the present study indicate, for the first time, that NPY is also present in a relatively high percentage of neuronal cells supplying the oesophagus. This suggests that NPY is an important neuronal factor, not only within the enteric nervous system located in the wall of the GI tract (El-Salhy and Hausken, 2016;Tan et al, 2018), but also in the extrinsic innervation of the digestive tract. It should be noted that, contrary to other segments of the GI system (Mikołajczyk et al, 2017), knowledge about the distribution and functions of NPY in the oesophagus is relatively limited (Parkman et al, 1989).…”
Section: Discussionmentioning
confidence: 99%